1999
DOI: 10.1046/j.1365-201x.1999.00595.x
|View full text |Cite
|
Sign up to set email alerts
|

Behavioural responses of γ‐MSH peptides administered into the rat ventral tegmental area

Abstract: The behavioural effects induced by alpha-, gamma1- and gamma2-MSH peptides (0.3 and 3 nmole per rat) injected into the left ventral tegmental area (VTA) of rats were compared. alpha- and gamma1-MSH caused grooming of comparable magnitude, and also additional vertical activity (rearing). By contrast gamma2-MSH caused a moderate but stable catalepsy, and practically no grooming. Moreover, intra-VTA pre-treatment with gamma2-MSH, 15 min prior to intra-VTA gamma1-MSH, markedly attenuated both the gamma1-induced gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…This is supported by studies first conducted in the 1980s showing that intra-VTA injection of α-MSH increases dopamine turnover in the NAc (Torre & Celis, 1986, 1988. Furthermore, intra-VTA α-MSH and MC3/4R agonists increase dopamine-dependent behaviours, such as rearing, grooming and locomotor activity (Torre & Celis, 1986, 1988Klusa et al 1999;Sanchez et al 2001). Additional evidence indicates that the melanocortin and mesocorticolimbic dopamine systems interact.…”
Section: Introductionmentioning
confidence: 81%
See 2 more Smart Citations
“…This is supported by studies first conducted in the 1980s showing that intra-VTA injection of α-MSH increases dopamine turnover in the NAc (Torre & Celis, 1986, 1988. Furthermore, intra-VTA α-MSH and MC3/4R agonists increase dopamine-dependent behaviours, such as rearing, grooming and locomotor activity (Torre & Celis, 1986, 1988Klusa et al 1999;Sanchez et al 2001). Additional evidence indicates that the melanocortin and mesocorticolimbic dopamine systems interact.…”
Section: Introductionmentioning
confidence: 81%
“…Previous studies have shown that intra‐VTA α‐MSH increases dopamine release in the NAc and dopamine‐dependent behaviours, suggesting that α‐MSH increases VTA dopamine neuron activity (Torre & Celis, , ; Klusa et al . ; Lindblom et al . ; Sanchez et al .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As mentioned above, icv injection of ACTH, ␣MSH, or MTII increases grooming and rearing behavior (Torre and Celis, 1986;Van Wimersma Greidanus et al, 1989) through a process that has been reported to be dependent on activation of D1Rs (Van Wimersma Greidanus et al., 1989). Subsequent studies have demonstrated that injection of ␣MSH or MTII directly into the VTA also increased grooming and rearing activity through a process that appears to depend on increased dopamine transmission (Adan et Klusa et al, 1999;Sanchez et al, 2001;Celis, 1986, 1988), and a subset of these studies have indicated that intra-VTA injection of ␣MSH also increases overall locomotor activity (Sanchez et al, 2001;Torre and Celis, 1986). In addition to the increased grooming and rearing observed following injection of ␣MSH into the VTA, intra-VTA ␣MSH also has been widely shown to increase dopamine release and turnover at efferent target sites, such as the nucleus accumbens and prefrontal cortex (Jansone et al, 2004;Lindblom et al, 2001;Sanchez et al, 2001;Celis, 1986, 1988;Yang and Shieh, 2005).…”
Section: Injection Of ˛Msh Directly Into the Vtamentioning
confidence: 97%
“…icv ACTH, MTII, ␣MSH Increased grooming and rearing Torre and Celis (1986) and Van Wimersma Greidanus et al (1989) ␣MSH/MTII to VTA Increased grooming and rearing Adan et al (1999), Klusa et al (1999), Sanchez et al (2001), and Celis (1986, 1988) ␣MSH/MTII to VTA Increased dopamine turnover Jansone et al (2004), Lindblom et al (2001), Sanchez et al (2001), Celis (1986, 1988), and Yang and Shieh (2005) MC3R −/− Increased activity Increased wheel running Butler et al (2000) and Chen et al (2000) Alcohol:…”
Section: Activitymentioning
confidence: 98%